PKM Terpadu di Desa Mekarbuana: Meningkatkan Karakter Masyarakat melalui Edukasi dan Aktivitas Sosial - Ahmad Pramegia; Dwi Kristanto; Pambuko Naryoto; Maruji Pakpahan; Hasan Ipmawan; Aris Wahyu Kuncoro; Muhammad Jusman Syah; Said Said; Andreas Wijaya; Annisa Nur Wahyuningsih (Pusat Riset dan Inovasi Nasional, 2025)
The Integrated Community Service Program (PKM) in Mekarbuana Village, Tegalwaru District, Karawang Regency, was implemented to enhance community character through education, digitalization, and social activities. The program included training on village website management, digital population census, environmental education, and the non-formal learning activity “Belajar Ceria”. The results indicate an improvement in digital literacy, social participation, and environmental awareness among villagers. The establishment of the village website and population data digitalization strengthened technology-based governance, while social and religious activities fostered solidarity and moral values in the community. This program demonstrates that collaboration between universities, local government, and the community can create sustainable social transformation.